Austrochthonius transversus Beier 1964 ... - Novák, János; Dányi, László (Zenodo, 2018)
transversus Beier, 1964 Austrochthonius chilensis transversus Beier 1964: 488, fig. 1. Syntypes. HNHM Pseudoscorp-44: 5 ex. [3 ♂, 1 ♀, 4 nymphs according to original description] “ Austrochthonius transversus n. sp., det. Beier, ♂ ♀, Typen!”, “No. 42.” [Argentina, Rio Negro, El Bolsón, Mt. Piltriquitron, 1150 m, from leaf litter in a forest of Maytenus boaria with Berberis darwini and Nothofagus antarctica close to a spring, 16.XI.1961, leg. Gy. Topál]. HNHM Pseudoscorp-45: 4 ex. [2 ♂, 8 ♀, 5 nymphs according to original description] “ Austrochthonius transversus n. sp., det. Beier, ♂ ♀, Paratypen ”, “No. 24.” [Argentina, Rio Negro, El Bolsón, Mt. Piltriquitron, 1500 m, leaf litter in a Nothofagus pumilio forest, 23.X.1961, leg. Gy. Topál]. HNHM Pseudoscorp- 46: 3 ex. [3 ♂, 7 ♀, 1 nymph according to original description] “ Austrochthonius transversus n. sp., det. Beier, ♂ ♀, Paratypen ”, “No. 19.” [Argentina, Mt. Piltriquitron, 1100 m, leaf litter in a bog forest of Nothofagus antarctica, 1. VII.1961, leg. ... : Published as part of Novák, János & Dányi, László, 2018, Catalogue of the type material of pseudoscorpions (Arachnida: Pseudoscorpiones) deposited in the Hungarian Natural History Museum, Budapest, pp. 301-322 in Zootaxa 4527 (3) on page 317, DOI: 10.11646/zootaxa.4527.3.1, http://zenodo.org/record/2612201 ...